Cyclic Procedural Content Generation of Open Game Worlds - Bihorac, Oskar Alija; Jedvert, Oskar; Orell, Jenny; Ström, David; Willman, Oskar (My University, 2017)
This thesis has explored the possibility of cyclic procedural content generation in open game worlds. To reach this goal Chef, a generation prototype handling graph grammar, and Dish, a game prototype, has been created. By using these prototypes it is possible to generate and play open game worlds which uses cyclic procedural content generation for the placement of areas inside of the game world. To have better control over the generation we use concepts called rules, recipes, and cookbooks. During the development of these prototypes two useful design patterns were discovered, local matching and hierarchical graphs. Local matching allows for the application of multiple rules on the same subgraph. Hierarchical graphs allows for nodes to contain entire subgraphs. These allows the level designer to have a greater deal of control over the generation process. The implications of these findings might mean that cyclic procedural content generation and generative world building methods will become a larger part of the future game development process and result in level designers developing levels from a higher level of abstraction.
Keywords: Data- och informationsvetenskap; Computer and Information Science